PENGARUH UKURAN KAP DAN AUDITOR TENURE TERHADAP VALUE RELEVANCE DARI NILAI WAJAR - Hidayat, Taufik (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
This study examines the value relevance of fair value and whether the value relevance of fair value measured at quoted active market is higher than value measured at valuation techniques. We also examine whether the value relevance offair value with valuation techniques improves if auditor tenure is longer or financial statements are audited by a Big Four Firm. Hypothesis testing was conducted by a panel data based on model of Ohlson (1995). Using a sample of 147 companies listed on the Indonesia Stock Exchange from 2008-2011, resulting the general conclusion that fair value has value relevance, where the value relevance of fair value measured at quoted active market is higher than the valuation technique. Value relevance of fair value measured at valuation techniques will increase as auditor tenure increases or financial statements were audited by a Big Four Firm.